SOBRE EL ARMAZON CONJUNTIVO DE LA PLACENTA I PLACENTA DE ALGUNOS ANIMALES - MONCADA, ULISES (Instituto Nacional de Cardiología, CD MEXICO, DF, MEX, 1942)
An histologic study of the placenta of the mouse, rat, cow, dog, and human subject was made to determine if the placenta acts only as a permeable membrane or is also capable itself of metabolizing the permeating substances This first report is concerned
BOL INST ESTUD MED BIOL
Keywords: ARMAZON, CONJUNTIVO, PLACENTA, ANIMALES; CIENCIAS MEDICAS; MEDICINA; HISTOLOGIA ANIMAL